The Seroepidemiology of Toxoplasmosis in the Lower Fraser Valley of British Columbia - Eileen M Proctor; Satyendra N Banerjee (Canadian Journal of Infectious Diseases)
Objective: To determine the seroprevalence of toxoplasmosis in vegetarian and nonvegetarian members of different ethnic communities in the lower Fraser Valley of British Columbia.